TRADITIONAL KYRGYZ CULTURE: AN ONTOLOGICAL REVIEW (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In the article, the concept of culture is subjected to ontological analysis, as onethe original models of the world and the result of human activity. The variety of manifestationof cultural elements in the semantic space-time dimension is considered on the example of Kyrgyz traditional artistic phenomena.
Keywords: culture, Kyrgyz, “Manas”, music, ontology, society, tradition, philosophy, ethics.